Model sprejemanja celovitih informacijskih rešitev (ERPAM) po njihovi uvedbi s strani uporabnikov - Sternad, Simona (Naše gospodarstvo, 2008)
Competition, rapid changes in business, obsolete information systems, etc. are just some of the many reasons that so many organisations have decided to replace obsolete IS''s with enterprise resource planning solutions (ERP solutions). Because of the complexity and size of ERP solutions, it is very important that organisations devote a lot attention to the selection and implementation of ERP solutions and their use. Nevertheless, it has been mentioned several times in the literature that successful use of ERP solutions depends on users themselves. A review of literature in the field does not show clear answers to the question of which factors and in what dimension they influence the acceptance and use of ERP solutions.
Keywords: podjetja; elektronsko poslovanje; informacijski sistemi; information technology; informacijska tehnologija; konkurenčnost